Case report: Rare abernethy malformation with hepatopulmonary syndrome in a pediatric patient - Ji, Lianfu; Ji, Zhaoming; Xiang, Dandan; Qin, Yuming; Yang, Shiwei (Frontiers in Pediatrics, 2022)
Abernethy malformation is a rare abnormality of the hepatic portal vein system with non-specific and diverse clinical manifestations. Here, we described a case of abernethy malformation with hepatopulmonary syndrome in a 10-year-old girl. On physical examination, cyanosed lips and acropachy could be found. Her oxygen saturation fluctuated at 89–94%, and the fasting blood ammonia was 98 umol/L. Furthermore, there were abnormalities in the imaging. The microbubble test with contrast echocardiography was positive. Computer tomography angiography (CTA) showed the splenic vein, and the superior mesenteric drained directly into the inferior vena cave after confluence. The same result was also observed in delayed splenic arteriography. Then, we discovered a tiny branch of the intrahepatic portal vein by the inferior vena cava balloon occlusion test, which could also show the confluence of the splenic vein and superior mesenteric vein with the inferior venacave. According to the evidence above, we concluded that the girl was a patient of type II abernethy malformation. For the severe dysplasia of the portal vein, the girl accepted partial ligation of portosystemic shunt and Rex shunt, which improved her oxygen saturation and exercise tolerance.